Pengaruh Ukuran Perusahaan, Ukuran KAP, Profitabilitas, Solvabilitas dan Komite Audit terhadap Audit Delay - Adinda Zahra Ristiara Zen; Arief Himmawan Dwi Nugroho (Universitas Muhammadiyah Metro, 2025)
Non-compliance of public listed companies in rthe publication of audited financial statements still occurs, for example in properties & real estate companies in Indonesia. This event is called audit delay and occurred consistently from 2019 to 2022. This study was conducted to analyze and prove the impact of lcompany size, KAP size, profitability, solvency and audit committee on audit delay in IDX-listed properties & real estate companies in 2019-2022. This study uses the population of properties & real estate companies listed on the IDX for 2019-2022 and purposive sampling techniques as sampling methods. 24 companies were obtained as samples with a research time of 4 years. The Partial Least Square approach and data analysis methods in the form of SEM were used to analyze research data. The result obtained is that the size of the company negatively affects the audit delay while other variables have no effect. For this, large category companies have a short delay span because they have a better internal control system